The Mechanisms for Realizing the Best Interests of the Child in Mediation - Bezhitashvili, Mariam (Alternative Dispute Resolution Yearbook, 2025)
The article examines the extent to which the principle of the best interests of the child is effectively implemented in the mediation process, and to what degree existing legal and practical mechanisms ensure the actual realization of this principle. It discusses the instruments and procedural safeguards through which the protection of the child’s interests can be achieved and evaluates their effectiveness from both theoretical and practical perspectives. Particular attention is given to the roles of the mediator, the parties to the mediation, and their representatives in ensuring the child’s best interests. The significance of the mediator’s professional competence, impartiality, and child-sensitive approach is analyzed, as well as the responsibility of the parties to avoid violating the child’s rights and interests during the process. The article also explores the legal and practical challenges related to the child’s right to be heard and to participate in mediation. These include the issue of summoning the child to mediation sessions and the associated risks, problems in determining the appropriate age threshold, ensuring the voluntariness of the child’s participation, the influence of parents on the formation of the child’s position, and the mediator’s competence to ensure the free and protected expression of the child’s views. The analysis of these issues aims to identify the circumstances that either facilitate or hinder the effective protection of the child’s best interests within the framework of mediation.